Synthesis, anticancer activity and ADMET studies of N-(5-methyl-1,3,4-thiadiazol-2-yl)-4-[(3-substituted)ureido/thioureido] benzenesulfonamide derivatives - KAYMAKÇIOĞLU, BEDİA; TOK, FATİH; KARAKUŞ, SEVGİ (TAYLOR & FRANCIS LTD, 2018)
A series of novel 4-[(3-substituted)ureido]-N-(5-methyl-1,3,4-thiadiazol-2-yl) benzenesulfonamides and 4-[(3-substituted)thioureido]-N-(5-methyl-1,3,4-thiadiazol-2-yl)benzenesulfonamides were prepared from 4-amino-N-(5-methyl-1,3,4-thiadiazol-2-yl)benzenesulfonamide (sulfamethizole). The structures of the synthesized compounds were determined by IR, H-1-NMR, MS and elemental analysis. The anticancer activity of these compounds was evaluated against human colorectal carcinoma (HCT116) and human cervix carcinoma (HeLa) cell lines. Compound 4 (4-{[(2,4-dichlorophenyl)carbamoyl]amino}-N-(5-methyl-1,3,4-thiadiazol-2-yl)benzenesulfonamide) showed marked anticancer activity, being the most active compounds in this series with the IC50 value of 13.92 +/- 0.22 mu M and 37.91 +/- 0.10 mu M against HeLa and HCT116, respectively. In silico, ADMET was used to examine their pharmacokinetic properties. ADMET (absorption, distribution, metabolism, excretion, and toxicity) studies were applied to develop new anticancer compound(s) with high selectivity. [GRAPHICS] .
Keywords: Urea; thiourea; anticancer activity; in silico ADMET; BIOLOGICAL EVALUATION; MOLECULAR DOCKING; AGENTS; SULFONAMIDES; INHIBITORS; DISCOVERY; THIOUREAS; CURCUMIN; UREA